Level of customer satisfaction on the service quality personal trainer - Abiyyu Amajida; Yudik Prasetyo; Enggista Hendriko Delano; Muhammad Fatih Humam (Jurnal Keolahragaan, 2022)
This research intends to identify customer satisfaction with the service quality provided by the personal trainers. This research was arranged based on theoretical studies related to the level of customer satisfaction with a particular service. The research was a descriptive quantitative study with a survey method and a questionnaire as the research instrument. This study was done in Health and Sports Center Universitas Negeri Yogyakarta (HSC UNY) Fitness Center. Purposive sampling was used to do sampling on this research. Criteria of the samples were customers who used the services of a personal trainer at the HSC UNY Fitness Center, and the personal trainers were registered as employees of the facility. The sample size consisted of 15 people out of the total population of 700 people. Research data were analyzed by the Likert scale method. The validity and reliability tests of the questionnaire obtained a validity value of 0.875 and 40 valid statement items out of a total of 50 statement items. The result of data analysis showed that the level of customer satisfaction with the service quality of personal trainers is Very Satisfactory, with a mean score of 87% for all aspects. The tangible element scored 87%, the reliability aspect scored 88%, the responsiveness aspect scored 89%, the assurance aspect scored 88%, and the empathy aspect scored 81%. This study suggested that personal trainers improve their service quality to the customers to increase the number of customers.